Efficient photoelectrochemical reduction of carbon dioxide into alcohols assisted by photoanode driven water oxidation with gold nanoparticles decorated titania nanotubes. Issue 52 (October 2021) - Karthick Raj, A.G.; Murugan, C.; Pandikumar, A.
Graphical abstract: In this work, a gold nanoparticle incorporated titanium dioxide nanotubes (Au@TNT) were used as a photoanode along with platinum cathode for the photoelectrochemical conversion of CO2 into methanol and ethanol with high product yield rate of 5.1 and 1.4 mM, respectively, for 2 h under AM 1.5 G illumination at the applied potential of +1 V vs Ag/AgCl. Highlights: Fabrication of Au NPs decorated TiO2 nanotube array via electrochemical method. Au@TNT electrode used as a photoanode in PEC CO2 reduction. Formation of Schottky barrier between the TiO2 and Au. Au@TNT photoanode shows photocurrent density of 0.826 mA cm −2 at +0.6 V vs. Ag/AgCl under illumination of AM 1.5G. Au@TNT photoanode driven PEC cell yields 5.1 mM of methanol and 1.4 mM of ethanol in 2 h illumination at +1 V vs. Ag/AgCl. Abstract: Production of small molecule alcohol via photoelectrochemical (PEC) conversion of carbon dioxide (CO2 ) is one of the most prominent way to reduce the atmospheric CO2 into emission freeway. In this work, a gold nanoparticle incorporated titanium dioxide nanotubes (Au@TNT) were used as a photoanode along with platinum cathode for the photoelectrochemical conversion of CO2 into methanol and ethanol with high product yield rate of 5.1 and 1.4 mM, respectively, for 2 h under AM 1.5 G illumination at the applied potential of +1 V vs . Ag/AgCl. The Au@TNTs were prepared by facile one step electrodeposition method, the introduction of Au nanoparticles on the TNT surface improve the conductivity, charge separation efficiency, improved the interfacial charge transfer process thereby reduced the recombination rate. The charge transfer mechanism in Au@TNT and the possible reaction at the electrode surface were investigated in detail.